2018
DOI: 10.1038/s41398-018-0160-4
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study on deep brain stimulation of the medial forebrain bundle for treatment-resistant depression

Abstract: Deep brain stimulation (DBS) to the superolateral branch of the medial forebrain bundle (MFB) has been reported to lead to rapid antidepressant effects. In this longitudinal study, we expand upon the initial results we reported at 26 weeks (Fenoy et al., 2016), showing sustained antidepressant effects of MFB DBS on six patients with treatment-resistant depression (TRD) over 1 year. The Montgomery-Åsberg Depression Rating Scale (MADRS) was used as the primary assessment tool. Deterministic fiber tracking was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 45 publications
2
75
1
Order By: Relevance
“…Thirteen studies were excluded because they did not compare active to sham stimulation [31][32][33][34][35][36][37][38][39][40][41][42][43], and one study was excluded as it included only three patients [44]. Therefore, 12 studies [15][16][17][18][19][20][21][22][23][24][25] (186 unique patients) were included in the meta-analysis and meta-regression ( Table 1). The Raymaekers et al study was analyzed as two separate studies, because this study included two anatomically distinct stimulation targets, and both targets were evaluated with blinded stimulation periods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies were excluded because they did not compare active to sham stimulation [31][32][33][34][35][36][37][38][39][40][41][42][43], and one study was excluded as it included only three patients [44]. Therefore, 12 studies [15][16][17][18][19][20][21][22][23][24][25] (186 unique patients) were included in the meta-analysis and meta-regression ( Table 1). The Raymaekers et al study was analyzed as two separate studies, because this study included two anatomically distinct stimulation targets, and both targets were evaluated with blinded stimulation periods.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple human trials have explored the efficacy of DBS for TRD. Anatomic targets have included the ventral anterior limb of the internal capsule (vALIC) [15], ventral capsule/ventral striatum (VC/VS) [16], subcallosal cingulate (SCC) [17][18][19][20][21][22], inferior thalamic peduncle (ITP) [23], medial forebrain bundle (MFB) [24,25], and lateral habenula [26]. Reports regarding the efficacy of DBS for TRD have been mixed, with some studies demonstrating encouraging results, while others have shown a lack of efficacy relative to sham stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a specific part of the MFB that has the maximum traffic of fibers–the supero‐lateral branch of the MFB–was proposed as a new DBS target . And as discussed in the previous section, deterministic tractography has been shown to help guide targeting of this particular tract with good clinical outcomes . In addition, whole‐brain activation volume probabilistic tractography has been shown to identify a combination of white matter tracts passing through the SCC target that mediate successful response to DBS for depression .…”
Section: Finding New or Optimal Neuromodulation Targets Based On Dtimentioning
confidence: 99%
“…Increased depression was associated with battery depletion in four patients, and accidental deactivation in three. 101 Evaluation of the tractographies showed that responders typically have their active contacts exclusively situated in the center of the triangle, with no contact with the nuclear environment. Thus, every treatment should be based on individual slMFB (tractography) geometry.…”
Section: Resultsmentioning
confidence: 99%